Ecological Momentary Assessment of Acute Alcohol Use Disorder Symptoms: Associations With Mood, Motives, and Use on Planned Drinking Days - Dvorak, Robert D. (Exp Clin Psychopharmacol, 2014)
Several theories posit that alcohol is consumed both in relation to one’s mood and in relation to different motives for drinking. However, there are mixed findings regarding the role of mood and motives in predicting drinking. Ecological momentary assessment (EMA) methods provide an opportunity to evaluate near real-time changes in mood and motives within individuals to predict alcohol use. In addition, endorsement of criteria of an alcohol use disorder (AUD) may also be sensitive to changes within subjects. The current study used EMA with 74 moderate drinkers who responded to fixed and random mood, motive, alcohol use, and AUD criteria prompts over a 21-day assessment period. A temporal pattern of daytime mood, evening drinking motivation, and nighttime alcohol use and acute AUD symptoms on planned drinking days was modeled to examine how these associations unfold throughout the day. The results suggest considerable heterogeneity in drinking motivation across drinking days. Additionally, an affect regulation model of drinking to cope with negative mood was observed. Specifically, on planned drinking days, the temporal association between daytime negative mood and the experience of acute AUD symptoms was mediated via coping motives and alcohol use. The current study found that motives are dynamic, and that changes in motives may predict differential drinking patterns across days. Further, the study provides evidence that emotion-regulation-driven alcohol involvement may need to be examined at the event level to fully capture the ebb and flow of negative affect motivated drinking.